Perspectives on Knowledge Representation in Maritime Education: A Qualitative Exploration of STIP Jakarta Cadets - Marudut Bernadtua Simanjuntak (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2023)
This research investigates the perspectives of 240 Maritime Institute Jakarta (STIP Jakarta) cadets regarding knowledge representation in navigational decision support systems. Grounded in a qualitative descriptive approach, the study unfolds over three semesters, examining academic self-checked intelligence, professional competences, motivations, and the cadets' viewpoints on the complexities of maritime education. The cadets, enrolled in an international programme, undergo extensive preparation for internships within the global shipping industry, necessitating proficiency in English communication aligned with International Maritime Organization standards. The findings reveal a positive correlation between academic self-checked intelligence and professional competences, underscoring the significance of metacognitive strategies in shaping technical proficiency. Motivations, both intrinsic and extrinsic, emerge as crucial influencers shaping cadets' perspectives on knowledge representation. The study also highlights the evolving confidence of cadets in English maritime literacy, emphasising the necessity of tailored language instruction strategies. Recommendations for enhancing maritime education include promoting metacognitive strategies, integrating real-world applications, tailoring language instruction, providing continuous motivational support, and ensuring regular curriculum reviews. These recommendations offer practical insights for educators and administrators to refine instructional practices and align curricula with industry demands.While acknowledging limitations such as reliance on self-reported data and the focus on a specific cohort, this research contributes to the discourse on maritime education. It serves as a foundation for future studies, urging a diversified methodology and extending the scope to include multiple maritime institutions for a more comprehensive understanding. As STIP Jakarta continues to prepare cadets for global maritime challenges, the insights gleaned from this study are integral for adapting and advancing educational practices.